2017
DOI: 10.1371/journal.pone.0169624
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Targeting of CD52 and TNF Allows Early Minimization Therapy in Kidney Transplantation: From a Biomarker to Targeting in a Proof-Of-Concept Trial

Abstract: BackgroundThere is high medical need for safe long-term immunosuppression monotherapy in kidney transplantation. Selective targeting of post-transplant alloantigen-(re)activated effector-T cells by anti-TNF antibodies after global T cell depletion may allow safe drug minimization, however, it is unsolved what might be the best maintenance monotherapy.MethodsIn this open, prospective observational single-centre trial, 20 primary deceased donor kidney transplant recipients received 2x20 mg Alemtuzumab (d0/d1) fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In the field of transplantation, there is an emerging interest in enhancing the suppressor immune response as an alternative strategy to reach a clinical tolerogenic state and preserve long‐term graft function . The immunosuppressive action of rapamycin has been already described in different mouse models of transplantation and, in this study, we have characterized the immunomodulatory effects of PI‐103 and PKI‐587 in T‐cells in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 92%
“…In the field of transplantation, there is an emerging interest in enhancing the suppressor immune response as an alternative strategy to reach a clinical tolerogenic state and preserve long‐term graft function . The immunosuppressive action of rapamycin has been already described in different mouse models of transplantation and, in this study, we have characterized the immunomodulatory effects of PI‐103 and PKI‐587 in T‐cells in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 92%
“…Beyond pilot analyses conveyed only in abstract form, the Berlin group performed a small trial to test the safety and efficacy of an immunosuppressive regimen that included alemtuzumab induction and day 2 post-transplant IFX to minimize immunosuppression. 41 The results suggested that the combined therapy permitted long-term graft survival in five patients treated with maintenance TAC monotherapy. Although intriguing, the small size and study design were insufficient to determine efficacy of the IFX therapy within the entire study regimen.…”
Section: Discussionmentioning
confidence: 93%
“…described a patient who was diagnosed with acute rejection weeks after having stopped all his medication, despite favourable CTL results . Nevertheless, several longitudinal studies support the idea that the assessment of direct T cell responses by CTL‐derived or IFN‐γ ELISPOT methods might be a valuable tool in predicting limited uneventful drug tapering, either from steroids , anti‐metabolite or calcineurin inhibitors .…”
Section: Biomarkers: Somewhere Between Hope and Realitymentioning
confidence: 99%